INSTITUTIONAL ROLE IN RELATION TO LEGAL POLICY TOWARDS OF CHILDREN’S RIGHTS TO EXCLUSIVE BREASTFEEDING - Lenny Syahnimar (Faculty of Law Universitas Lampung, 2020)
Breastfeeding is one of the best buys in global health to save lives and improve the health, social, and economic development of individuals and nations. Inadequate breastfeeding impacts a child’s ability to learn, and consequently, their future earning potential. By supporting mothers to practice proper breastfeeding, nearly 50 per cent of under two child deaths caused by diarrhoea and pneumonia could be prevented annually compared to a situation with no breastfeeding. This study aims to understand and analyze the role institutions and legal policy towards the fulfilment of children’s rights to exclusive breastfeeding. This research is normative-empirical legal research. Primary data was obtained through interviews with sources, while secondary data is attained through literature studies on legal material. Data analysis is carried out with a qualitative approach. Results: Institutional is a set of rules of all levels that revolve around a fundamental need in the social life of society. The institutional role is to meet the basic needs of citizens regarding an order, guidelines on how to behave, and as social control. Legal rule the exclusive Nursing program policy is based on the provisions of the Law No. 36 of 2009 with the form of regulation through Government Regulations No. 33 of 2012.